1984 [compact disc, unabridged] - Orwell, George, 1903-1950 (Blackstone Audio, 2007)
Portrays a terrifying vision of life in the future when a totalitarian government, considered a "Negative Utopia," watches over all citizens and directs all activities, becoming more powerful as time goes by.